Kajian kualitas air lindi terhadap kualitas air tanah di sekitar tpa (tempat pemrosesan akhir) sampah jetis, desa pakem, kecamatan gebang, purworejo, jawa tengah - Ika Wahyuning Widiarti; Eni Muryani (Universitas Pembangunan Nasional Veteran Yogyakarta, 2018)
Study Of Leachate Quality to Groundwater Quality Around Jetis Landfill, Pakem, Gebang District, Purworejo Regency, Central Java Province (Ika Wahyuning Widiarti and Eni Muryani): Organic waste will be decomposed easily and produce leachate. Leachate may pollute soil, groundwater and river around TPA (Final Disposal) Jetis if it does not manage well. The objectives of this research are to describe leachate quality with parameters pH, BOD, COD, TSS, N-Total, Hg and Cd, to analyse the status of groundwater quality, and to evaluate the connection between leachate quality and groundwater quality around TPA Jetis. Leachate sampling was conducted at inlet and outlet of WWTP of TPA Jetis and the groundwater sampling was conducted at resident well and monitoring well. Research result showed that parameters BOD, COD, and TSS at inlet exceeded the standard. While the all parameters of the outlet were still meet the standard. The status of groundwater quality included lightly polluted with PI for monitoring well was 1.082 and for resident well was 2.912. Laboratory results showed that the resident well has BOD and COD values that exceed the standard. So that it can be expected that groundwater contamination occurs because of leachate from the TPA Jetis so that the groundwater quality of the resident well around the landfill decreases.